CNS Immune Profiling in a Dengue Virus-Infected Immunocompetent Outbred ICR Mice Strain - Shen, Ting-Jing; Chen, Chia-Ling; Jhan, Ming-Kai; Tseng, Po-Chun; Lin, Chiou-Feng (Frontiers in Cellular and Infection Microbiology, 2020)
Dengue virus (DENV) infection in the brain causes severe dengue disease with neuropathic complications. In addition to viral effects, immunogenic or pathogenic central nervous system (CNS) inflammation can be induced during DENV infection. By using an immunocompetent outbred ICR (Institute of Cancer Research) mouse model for investigating CNS immunity upon DENV infection, we conducted single-panel immune cell profiling and a multiplex cytokine assay. The ICR mice infected with DENV presented with progressive hunchback posture, limbic seizures, limbic weakness, paralysis, and lethality. When the virions were released, the viral non-structural protein 1 was expressed in the brain in a time-dependent manner. Isolated brain CD45-positive cells revealed a significant population of resident CD14-positive cells, which was considerably decreased 8 days post-infection. We found an unexpected time-kinetic decrease in CD19-positive cells and CD11c/MHC II-positive cells and an increase in NK1.1-positive cells. Further assays showed the time-dependent induction of proinflammatory and NK1.1-associated cytokines in the DENV-infected brains. These results indicate a CNS immune profile of DENV infection and hypothetical CNS immunity in response to DENV infection.